Effects of in ovo Injection of Astragalus Polysaccharide on the Intestinal Development and Mucosal Immunity in Broiler Chickens - Yang, Shu-bao; Qin, Yan-jun; Ma, Xin; Luan, Wei-min; Sun, Peng; Ju, An-qi; Duan, Ao-yi; Zhang, Ying-nan; Zhao, Dong-hai (Frontiers in Veterinary Science, 2021)
The purpose of this study was to examine the effects of in ovo injection of Astragalus polysaccharide (APS) on hatchability, body weight (BW), intestinal histomorphology, the number of IgA+ cells and sIgA content in intestine, and the expression of intestinal immune-related genes in broiler chickens. On day 18 of the incubation, a total of 960 live embryo eggs were weighed and randomly divided into 4 treatment groups: a control group and three APS groups. The eggs in the control group were injected with 0.5 mL physiological saline. The eggs in the APS groups were injected with 3 different amounts of APS in 0.5 mL physiological saline: 1 mg (APSL), 2 mg (APSM) and 4 mg (APSH). The solution was injected into the amnion of each egg. The results showed that in ovo injection of APS did not affect the hatchability but increased the body weight of the 14 d and 21 d chickens, with a significant increase observed in the APSM group (P < 0.05). Compared with the control group, the villus height (VH) was increased (P < 0.05) and the crypt depth (CD) was decreased (P < 0.05) in the small intestine of the broilers, with higher VH/CD ratios in the APS groups. The number of IgA+ cells in the mucosa and the secretory immunoglobulin A (sIgA) levels in the intestinal washings were higher in the APSM and APSH groups than in the APSL and control groups. The gene expression levels of interleukin (IL)-2, interleukin (IL)-4, interferon gamma (IFN-γ) and Toll-like receptor (TLR)-4 were significantly enhanced by APS stimulation at most time points (P < 0.05). These results indicated that in ovo injection of APS has the potential of promoting intestinal development and enhancing intestinal mucosal function of broiler chickens in the early stage after hatching.